Agreement of caudal aortic arterial blood pressure with oscillometry using two cuff widths placed on the thoracic or pelvic limbs of sevoflurane-anesthetized rabbits. (July 2022) - Desprez, Isabelle; Pelchat, Jennifer; Beaufrère, Hugues; Beazley, Shannon G.; Duke-Novakovski, Tanya
Abstract: Objective: To evaluate agreement with central systemic arterial pressure of an oscillometer and two cuff widths placed on the thoracic or pelvic limbs. Study design: Prospective experimental study. Animals: A group of nine New Zealand White rabbits weighing 3.5 ± 0.3 kg. Methods: Rabbits were sedated with dexmedetomidine and midazolam, then anesthetized with ketamine and sevoflurane. The femoral artery was surgically exposed and a 20 gauge, 5 cm catheter inserted to measure systolic (SAP), mean (MAP) and diastolic (DAP) blood pressure at the iliac artery and caudal aorta junction. Adjustments of vaporizer dial and dobutamine infusion provided a range of invasive blood pressure (IBP). Two measurements of IBP were recorded during the oscillometer cycling phase, and the mean value was used in analyses. Oscillometer cuffs of bladder width 2.0 cm (S1) and 2.5 cm (S2) were placed proximal to the carpus and tarsus. Cuff width to circumference ratio was calculated. Oscillometer SAP, MAP and DAP were paired with corresponding IBP values. Agreement was assessed using linear mixed models ( p < 0.05). Results: Cuff ratios for both limbs were 41% (S1 cuff) and 50% (S2 cuff) and 122–139 paired observations were obtained. There was significant limb × cuff interaction with SAP and MAP. The oscillometer overestimated SAP and MAP on the pelvic limb and underestimated SAP and MAP on the thoracic limb. For SAP, the oscillometer overestimated by constant bias (–19 ± 2 mmHg) and proportional bias (0.28 ± 0.02 mmHg per 1 mmHg increase). For MAP, the oscillometer underestimated by constant bias (4 ± 2 mmHg) and was worse with S2 on the thoracic limb. Overestimation was similar between cuffs on the pelvic limb. For DAP, the oscillometer underestimated by constant bias (15 ± 2 mmHg). Conclusions and clinical relevance: Cuff S1 on the thoracic limb provided best estimation of MAP.